Plasmodium berghei ANKA: selection of resistance to piperaquine and lumefantrine in a mouse model. - BELL, ANGUS (Elsevier, 2009)
We have selected piperaquine (PQ) and lumefantrine (LM) resistant Plasmodium berghei ANKA parasite lines in mice by drug pressure. Effective doses that reduce parasitaemia by 90% (ED90) of PQ and LM against the parent line were 3.52 and 3.93 mg/kg, respectively. After drug pressure (more than 27 passages), the selected parasite lines had PQ and LM resistance indexes (I90) [ED90 of resistant line/ED90 of parent line] of 68.86 and 63.55, respectively. After growing them in the absence of drug for 10 passages and cryo-preserving them at ?80 ?C for at least 2 months, the resistance phenotypes remained stable. Cross-resistance studies showed that the PQ-resistant line was highly resistant to LM, while the LM-resistant line remained sensitive to PQ. Thus, if the mechanism of resistance is similar in P. berghei and Plasmodium falciparum, the use of LM (as part of Coartem?) should not select for PQ resistance.
PUBLISHED
Keywords: Malaria; Plasmodium berghei; Drug resistance; Cross-resistance; Lumefantrine; Piperaquine